A new species of the genus Parastylodactylus Figueira, 1971 (Crustacea: Decapoda: Caridea: Stylodactylidae) from off Kollam, southwest coast of India - Komai, Tomoyuki; Shanis, C. P. Rajool (Zootaxa, 2011)
A new species of the caridean genus Parastylodactylus Figueira, 1971 (Stylodactylidae), P. sulcatus, is described and illustrated on the basis of three male specimens from the Southern Arabian Sea, off the southwest coast of India, at a depth of 350 m. Morphologically, the new species appears closest to P. bimaxillaris (Bate, 1888) widely distributed in the IndoWest Pacific, but the much longer rostrum, the absence of a supraorbital tooth on the carapace, the deep hepatic groove on the carapace and the relatively longer and more slender third pereopod distinguish the new species from P. bimaxillaris. It is the first representative of the genus from Indian waters. An updated key to the species of Parastylodactylus is presented.